Laokoon in Literatur und Kunst : Schriften des Symposions "Laokoon in Literatur und Kunst" vom 30.11.2006, Universität Bonn - Gall, Dorothee; Wolkenhauer, Anja (Beiträge zur Altertumskunde, 2009)
The fate of the Trojan priest Laokoon was related in Antiquity by, among others, Sophocles, Virgil and Quintus Smyrnaeus. The rediscovery of the Laokoon statue group in Rome in 1506 led to numerous new works, including many in the visual arts. The contributions in the proceedings of the symposium presented here analyse key moments in the ancient and modern discourse on the story of Laokoon and the group of statues - as testimony to the magnificence of ancient art, fear or disdain of the gods, suffering, violence and the power of fate.